Planet ocean : a story of life, the sea, and dancing to the fossil record - Matsen, Bradford (Berkeley : Ten Speed Press, 1994)
Irreverent approach to the origins of life, using a fish story to begin the discussion of the Precambrian age, approximately 650 million years ago, and traveling on through dinosaurs, and finally, humans.
Includes bibliographical references (p. 125-127) and index.
Kliatt.
The Science Teacher (N.S.T.A.).
Young Adult
Keywords: Evolutionary paleobiology; Fossils -- North America; Evolution; Fossils